Praktik Tata Kelola Sekolah untuk Mendukung Peningkatan Mutu Pendidikan pada Sekolah Dasar Islam - Sukirdi Sukirdi; Ayu Wulandari; Hardianto Hardianto (Program Studi PGMI, Universitas Al Falah As Sunniyah Kencong Jember, 2024)
School governance plays a strategic role in achieving sustainable educational quality. Effective governance enables schools to optimize resources, improve educational services, and foster adaptive organizational cultures. This study aims to explore school governance practices in supporting educational quality improvement at Madani Integrated Islamic Elementary School. A qualitative case study design was employed. Simulated data for manuscript development were obtained through in-depth interviews with the principal, vice principal, teachers, school committee members, and parents, complemented by observations and document analysis. Data were analyzed using data reduction, data display, and conclusion drawing with source and method triangulation. The findings indicate that school governance is implemented through visionary leadership, participatory strategic planning, human resource management, quality culture development, and stakeholder partnerships. These practices contribute to improving instructional quality, teacher professionalism, organizational discipline, and parental satisfaction. Nevertheless, challenges remain in digital governance and data-driven evaluation systems. The study highlights that integrated school governance is fundamental